Platformisation of Mobile Operators Business Model: A Proposition Using Design Science Approach and Grounded Theory Principles - Hmoud, Aladeen Y. R.; Salim, Juhana; Yaakub, Mohd Ridzwan (International journal on advanced science, engineering and information technology, 2020)
Mobile network operators (MNOs) business models (BM) are under pressure due to their lesser capability of introducing superior values to their customers in the mobile ecosystem. However, recent research efforts in developing new BM advocate two-sided BM that encompasses the diversity of MNO’s activities and capabilities. As a result, a new multidisciplinary service-based two-sided BM needs to be developed that incorporates these activities and skills. The small body of the extant literature on the subject suggests that it may be possible to enhance MNOs' BM by combining contemporary information technology tools with managerial design principles and concepts. This study designs a two-sided mobile advertising BM to investigate the application of a big data-driven BM to transform MNOs' current one-sided BMs to two-sided ones. To accomplish this, it combines the design science research methodology (DSR), which aims to create a problem-solving artifact for real-world problems, and the grounded theory approach, which aims to develop substantive theory and increase the rigor of the design process. The initial BM was proposed using deductive and adductive reasoning from academic and grey literature. The results of this study have shown that the new BM can enhance their revenue streams and competitive edge. This study identified that successful BM should be built on established MNOs core competencies and business activities. This study showed the applicability of two-sided theory and big data-driven tools and technologies to create new superior value propositions to both advertisers and end-users and thus innovative BMs for MNOs. The paper concludes with the fundamental requirements to build a data-driven two-sided BM.